2019
DOI: 10.1155/2019/1970365
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Carbon-Based Electrode Material from Oil Palm Waste-Derived Reduced Graphene Oxide and Its Capacitive Performance Evaluation

Abstract: This paper is an expansion of our previous work on the synthesis of graphene oxides and reduced graphene oxides from different kinds of oil palm waste-based feedstocks, namely, OPL (oil palm leaf), PKS (palm kernel shell), and EFB (empty fruit bunch). Here, the electrochemical measurements of the resulting reduced graphene oxides derived via mild-temperature annealing reduction of the graphene oxides were accomplished using cyclic voltammetry and galvanostatic charge/discharge processes. The findings put forwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The peak at 1662 cm −1 was attributed to C C stretching in aromatic groups, while the peak at 1198 cm −1 was due to carboxyl C–O stretching vibrations. 49 The hydroxyl and carboxyl peaks in the rGOPKS FTIR spectrum indicated that oxidation occurred. The introduction of oxygen-bearing functional groups during rGOPKS formation demonstrated that surface modification with acidic and oxidative chemicals was successful.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at 1662 cm −1 was attributed to C C stretching in aromatic groups, while the peak at 1198 cm −1 was due to carboxyl C–O stretching vibrations. 49 The hydroxyl and carboxyl peaks in the rGOPKS FTIR spectrum indicated that oxidation occurred. The introduction of oxygen-bearing functional groups during rGOPKS formation demonstrated that surface modification with acidic and oxidative chemicals was successful.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of oxygen-bearing functional groups during rGOPKS formation demonstrated that surface modification with acidic and oxidative chemicals was successful. 49 …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, much smaller pore size distributions are found within other exfoliated graphitic materials. 11,[46][47][48] The average pore size, as determined by the BJH analysis, was found to be 10.4 nm (Table 3). Taking into account this average value in conjunction with the crystallite size, (35.5 nm) determined by XRD, it is understood that the thickness of a stack of MLG plus its associated slit pore equates to 45.9 nm.…”
Section: Surface Area and Porosity Analysismentioning
confidence: 99%